Modelling Energy demand for Policy Analysis - Jyoti K. Parikh (Planning Commission Government of India, 1980)
The study “Modelling Energy Demand for Policy Analysis” by Jyoti K. Parikh develops a comprehensive national energy modeling system for India to inform long-term policy and investment decisions. The system integrates a macro-economic model (SIMA), an energy demand model (ENDIM), and an investment model (INVEST) to simulate energy requirements across industries, transport, agriculture, and households. Key findings indicate substantial growth in energy demand driven by urbanization, industrialization, mechanized agriculture, and increasing household consumption of commercial energy. The models highlight sector-specific energy intensities, investment requirements, and the need for policy interventions such as efficiency improvements, promotion of rail transport, and optimization of energy imports. Regional disparities in energy availability and consumption are emphasized, suggesting targeted strategies for resource allocation. The study provides a forward-looking framework for sustainable energy management, aligning policy, investment, and technology choices to meet India’s growing energy needs.
Government of India Planning Commission New Delhi 1981
Keywords: Energy Demand; Energy Policy; India; Macro-Economic Model; ENDIM; INVEST; Industrial Energy; Transport Energy; Agricultural Energy; Household Energy; Investment Requirements; Regional Energy Distribution